RESPON FISIOLOGIS TANAMAN KANGKUNG AIR (Ipomoea aquatica Forssk.) PADA CEKAMAN LOGAM MERKURI - Muh. Shofi; Suharyanto Suharyanto (Universitas Sebelas Maret, 2014)
Abstract - The purpose of this study was to determine the effect of mercury stress on the physiological response of water spinach. This study use a completely randomized design (CRD) with 5 treatments Hg concentrations of heavy metals, namely 0, 1, 3, 5, and 7 ppm with 4 replicates for each treatment and were harvested after 15 and 30 days after planting. Observation parameters such as root length, stolon length, number of leaves, biomass, chlorophyll content, and mercury levels after 15 and 30 days. Data were analyzed using F test and DMRT test with a significance level of 5% with SPSS 15. The results showed that more hight concentrations of Hg is caused decreation of: root length, stolon length, number of leaves, biomass, chlorophyll content both on treatment 15 days or 30 days Hg stress. Highest levels of Hg found in the roots of both in treatment 15 days or 30 days compared between the stem and the leaves are at the root. It caused in root there is endodermis which serves as a filter heavy metals. The presence of mercury causes metabolism and physiological of water spinach disrupted. Keywords : water spinach (I. aquatica Forssk.), Hg, physiological response